IMPACT OF CRUCIFER PLANT EXTRACTS ON CHLOROPHYLL AND CAROTENOID CONTENTS OF AFLATOXIN B1 TREATED MAIZE SEEDS - Kumar, Mahesh; Prasad, Gajendra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research evaluates the phytotoxic effects of aflatoxin B1 on the chlorophyll and carotenoid contents of maize (Zea mays L.) seedlings and examines the protective potential of three crucifer plant extracts: A (Raphanus sativus), B (Lepidium sativum), and C (Brassica oleracea var. italica). Aflatoxin B1 treatment at 2000 µg/L reduced chlorophyll a by 0.470% (70.15%), chlorophyll b by 0.180% (64.29%), total chlorophyll by 0.652% (68.60%), and carotenoids by 0.016% (76.19%) compared to controls. Co-treatment with crucifer extracts significantly mitigated these losses, with extract C achieving the greatest restoration, reducing total chlorophyll inhibition to 0.330% (34.74%) and carotenoid inhibition to 0.009% (42.86%). Extracts alone slightly increased pigment levels, with C enhancing total chlorophyll by 0.060% (6.32%) and carotenoids by 0.003% (14.29%). These findings suggest that crucifer extracts, particularly C, serve as both enhancers and mitigators, offering a sustainable approach to counter aflatoxin B1-induced photosynthetic stress in maize cultivation, especially in aflatoxin-prone regions like Bihar, India.